2019
DOI: 10.1097/md.0000000000017439
|View full text |Cite
|
Sign up to set email alerts
|

The association of speckle-type POZ protein with lymph node metastasis and prognosis in cancer patients

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…26 A meta-analysis of nine studies including 928 patients with various cancers suggested that SPOP protein may be a useful prognostic biomarker in cancer patients. 27 We previously found that SPOP downregulation or S119N mutation resulted in loss of function in HB. We carried out various experiments to verify SPOP as an anti-oncogene and S119N as a loss-of-function mutation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…26 A meta-analysis of nine studies including 928 patients with various cancers suggested that SPOP protein may be a useful prognostic biomarker in cancer patients. 27 We previously found that SPOP downregulation or S119N mutation resulted in loss of function in HB. We carried out various experiments to verify SPOP as an anti-oncogene and S119N as a loss-of-function mutation.…”
Section: Discussionmentioning
confidence: 97%
“… 26 A meta-analysis of nine studies including 928 patients with various cancers suggested that SPOP protein may be a useful prognostic biomarker in cancer patients. 27 …”
Section: Discussionmentioning
confidence: 99%